The Effectiveness ESD-Oriented Learning Strategies with Local-Based Interactive Visual Media to Enhance Environmental sensitivity among Geography Students in Aceh - Zukya Rona Islami; Lailissa'adah; Ardhika Bestary Rizkiani (Scidac Plus, 2026)
This study aims to analyze the effectiveness of Education for Sustainable Development (ESD)-oriented learning supported by local-based interactive visual media in enhancing the environmental sensitivity of geography education students in Aceh. The study employed a quantitative approach using a quasi-experimental non-equivalent control group design involving 122 students from three universities in Aceh. The participants were divided into experimental and control groups. The experimental group received ESD-oriented learning integrated with local environmental issues and interactive visual media, while the control group received conventional learning. The research instrument consisted of an environmental sensitivity questionnaire based on local environmental case studies using a 4-point Likert scale. Data were collected through pretests and posttests and analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, and N-Gain analysis. The results revealed a significant improvement in the environmental sensitivity of students in the experimental group compared to the control group (p < 0.05). The experimental group achieved a moderate N-Gain score, while the control group showed a lower improvement. The findings indicate that ESD-oriented learning integrated with local-based interactive visual media is more effective in strengthening students’ environmental awareness, empathy, responsibility, and concern toward environmental issues. This study highlights the importance of contextual and interactive learning in promoting sustainable environmental education in higher education.